(untitled) (diségno, 2024)
In contemporary China, the historicity of places fears a fate like Yang Yongliang’s ‘Phantom Landscape’ series, which envision the dystopian consequences of the hyper-construction syndrome and market frenzy of late 20th century China. Nevertheless, the allure of cultural tradition still attracts the interest of a minority of independent firms that today embody the best practices in architecture, urban planning and landscape design in the country. In this scenario, in little more than five years, starting in 2007, ZAO/standardarchitecture has constructed a constellation of buildings in the Linzhi area of Tibet, with which it has responded to the request to boost the local tourist vocation with new accommodation facilities, experimenting with different forms of dialogue with the landscape of this remote autonomous region of China. The ‘pressure points’ of the architectural acupuncture prepared by Zhang Ke, owner of the indipendent firm founded in Beijing in 2001, are small- and medium-scale interventions that stand out for their ‘archaic’ modernity and for their profound understanding of the possibilities concealed in the interaction between architecture and indigenous building knowledge and techniques. Topographical sensitivity, with an almost geological matrix, inspires the settlement strategies of these architectural fragments, guaranteeing, without apparent effort, their sublimation in the hosting landscape.